Comparison of Critical Thinking Skills Using Active Deep Learning Experience and Inquiry Based Learning in Islamic Education - Marta Novika; Salmi Wati (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Critical thinking is a vital 21st-century skill that enables students to think creatively and logically. In Islamic Education, this skill often remains underdeveloped, especially in responding to higher-order thinking skills questions. This study examines differences in critical thinking skills between students taught using the Active Deep Learning Experience model and those taught with the Inquiry Based Learning model. Employing a quantitative quasi-experimental design, the research involved sixth-grade students. The findings reveal that: (1) the Active Deep Learning Experience is more effective than Inquiry Based Learning for students with high prior ability, with a significance value of 0.049 (<0.05); (2) the Active Deep Learning Experience is also more effective for students with low prior ability, with a significance value of 0.032 (<0.05); (3) students with low prior ability showed significant improvement, with a significance value of 0.040 (<0.05); and (4) no significant interaction was found between learning models and prior ability, with a significance value of 0.325 (>0.05). Overall, the Active Deep Learning Experience consistently demonstrates superiority in enhancing students’ critical thinking skills in Islamic Education, supported by its integration of national and integrated curricula to achieve holistic learning outcomes.